Phytogenic Additives Can Modulate Rumen Microbiome to Mediate Fermentation Kinetics and Methanogenesis Through Exploiting Diet–Microbe Interaction - Hassan, Faiz-ul; Arshad, Muhammad Adeel; Ebeid, Hossam M.; Rehman, Muhammad Saif-ur; Khan, Muhammad Sajjad; Shahid, Shehryaar; Yang, Chengjian (Frontiers in Veterinary Science, 2020)
Ruminants inhabit the consortia of gut microbes that play a critical functional role in their maintenance and nourishment by enabling them to use cellulosic and non-cellulosic feed material. These gut microbes perform major physiological activities, including digestion and metabolism of dietary components, to derive energy to meet major protein (65-85%) and energy (80%) requirements of the host. Owing to their contribution in digestive physiology, rumen microbes are considered one of the crucial factors affecting feed conversion efficiency in ruminants. Any change in the rumen microbiome has an imperative effect on animal physiology. Ruminal microbes are fundamentally anaerobic and produce various compounds during rumen fermentation, which are directly used by the host or other microbes. Methane (CH4) is produced by methanogens through utilizing metabolic hydrogen during rumen fermentation. Maximizing the flow of metabolic hydrogen in the rumen away from CH4 and toward volatile fatty acids (VFA) would increase the efficiency of ruminant production and decrease its environmental impact. Understanding of microbial diversity and rumen dynamics are crucial not only for the optimization of host efficiency but also required to mediate emission of greenhouse gases (GHGs) from ruminants. There are various strategies to modulate rumen microbiome, mainly including dietary interventions and the use of feed additives like plant secondary compounds. Phytogenic feed additives, mainly plant secondary compounds, have shown to modulate rumen microflora and change rumen fermentation dynamics leading to enhanced animal performance. Many in vitro and in vivo studies aimed to evaluate the use of plant secondary metabolites in ruminants have been conducted using different plants or their extract or essential oils. This review specifically aims to provide insights into the ecology of rumen microbes, their dietary interactions, and respective role in rumen fermentation. Moreover, a comprehensive overview of the modulation of rumen microbiome by using phytogenic compounds (essential oils, saponins, and tannins) for manipulating rumen dynamics to mediate methane emanation from livestock is presented. We have also discussed the pros and cons of each strategy along with future prospective of dietary modulation of rumen microbiome to improve the performance of ruminants while decreasing GHG emissions.